Answer:
The difference between the area of the original triangle and the area of the new triangle is 5(3x + 7)(5x - 1)/2
Step-by-step explanation:
We know that the area of a triangle A = 1/2bh where b = base and h = height.
Let A be the area of triangle 1 with base (3x + 7) and height (5x - 1).
So its area A = (3x + 7)(5x - 1)/2.
Now for the second triangle, the base is tripled, so its base is 3(3x + 7) and its height is doubled, so its height is 2(5x - 1)
So its area is A' = 3(3x + 7) × 2(5x - 1)/2 = 3(3x + 7)(5x - 1)
So the difference between the area of the original triangle and the new triangle is
A' - A = 3(3x + 7)(5x - 1) - (3x + 7)(5x - 1)/2
= (3x + 7)(5x - 1)(3 - 1/2)
= 5(3x + 7)(5x - 1)/2
So the difference between the area of the original triangle and the area of the new triangle is 5(3x + 7)(5x - 1)/2